A framework for the systematic consideration of ethics, equity, feasibility, and acceptability in vaccine program recommendations. Issue 36 (10th August 2020) - Ismail, Shainoor J.; Hardy, Kendra; Tunis, Matthew C.; Young, Kelsey; Sicard, Nadine; Quach, Caroline
Highlights: Practical, evidence-informed advice considers the spectrum of public health science. This framework fills a gap in the comprehensive development of vaccine guidance. It enables the systematic examination of ethics, equity, feasibility, and acceptability. In Canada, successful implementation has led to timely, transparent recommendations. These tools, based on extensive research, can be used by advisory groups worldwide. Abstract: For the successful implementation of population-level recommendations, it is critical to consider the full spectrum of public health science, including clinical and programmatic factors. Current frameworks may identify various factors that should be examined when making evidence-informed vaccine-related recommendations. However, while most immunization guidelines systematically assess clinical factors, such as efficacy and safety of vaccines, there is no published framework outlining how to systematically assess programmatic factors, such as the ethics, equity, feasibility, and acceptability of recommendations. We have addressed this gap with the development of the EEFA (Ethics, Equity Feasibility, Acceptability) Framework, supported by evidence-informed tools, including Ethics Integrated Filters, Equity Matrix, Feasibility Matrix, and an Acceptability Matrix. The Framework and tools are based on five years of environmental scans, systematic reviews and surveys, and refined by expert and stakeholder consultations and feedback. For each programmatic factor, the EEFA Framework summarizes the minimum threshold for consideration and when further in-depth analysis may be required, which aspects of the factor should be considered, how to assess the factor using the supporting evidence-informed tools, and who should be consulted to complete the assessment. Research, particularly in the fields of vaccine acceptability and equity, has validated the utility and comprehensiveness of the tools. The Framework has been successfully used in Canada for clear, timely, transparent vaccine guidance with positive stakeholder feedback on its comprehensiveness, relevance and appropriateness. Applying the EEFA Framework allows for the systematic consideration of the spectrum of public health science without a delay in recommendations, complementing existing decision-making frameworks. This Framework will therefore be useful for advisory groups worldwide to integrate critical factors that could impact the successful and timely implementation of comprehensive, transparent recommendations, and will further the global objective of developing practical and evidence-informed immunization policies.